2018
DOI: 10.11646/phytotaxa.358.3.5
|View full text |Cite
|
Sign up to set email alerts
|

New data on the genus Epipactis (Orchidaceae) in the North Caucasus with description of a new species

Abstract: A new self-pollinating species, Epipactis euxina, is described from Gelendzhik District of Krasnodar Territory. The species is closely related to E. persica from which it differs by its remarkable long pedicel, distinctly longer epichile, and indistinct or absent viscidium. It grows in sparse pine forest mixed with oak, on calcareous soils. Four other taxa collected in different localities of Krasnodar Territory are new for the North Caucasus: E. krymmontana, E. leptochila subsp. leptochila, E. leptochila subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
11
0
3
Order By: Relevance
“…Indeed, the differences between E. exilis and E. persica are not clear (cf. Fateryga et al, 2018b) and this is possibly true for other taxa as well. On the other hand, there are some species, which are well-recognized morphologically, e. g., E. euxina Fateryga, Popovich et Kreutz from the North Caucasus or the species from Crete known as E. cretica Kalop.…”
Section: Species Accountmentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, the differences between E. exilis and E. persica are not clear (cf. Fateryga et al, 2018b) and this is possibly true for other taxa as well. On the other hand, there are some species, which are well-recognized morphologically, e. g., E. euxina Fateryga, Popovich et Kreutz from the North Caucasus or the species from Crete known as E. cretica Kalop.…”
Section: Species Accountmentioning
confidence: 85%
“…1A-B). Study of the living plants in flower revealed that they had epichile rather equal in length and width, and distinctly present but inefficient viscidim, i. e., the characters of E. persica (Fateryga et al, 2018b). One more character is a short but distinctly present pedicel.…”
Section: Species Accountmentioning
confidence: 99%
“…Distribution, occurrence and habitats in the study area. This species is known only from the type locality (NS) in the nature monument «Roshcha sosny pitsundskoy "Dzhankhotskaya"»: «Gelendzhik District, vicinity of khutor Dhzankhot, Mt Svyataya Nina» (Fateryga et al, 2018b).…”
Section: Nomenclature List Of Orchidaceae Taxamentioning
confidence: 99%
“…Schlechter [Nazarov, 1995;Fateryga et al, 2013], что может свидетельствовать о значительной древности этих ос. Веспидофильный синдром опыления известен также у некоторых видов растений рода Scrophularia [Fateryga, 2011], видов рода Epipactis [Fateryga, Ivanov, 2012], что указывает на глубокие лектические связи между осами-веспидами и цветковыми растениями.…”
unclassified
“…Сведения о кормовых растениях ос-веспид палеарктической фауны содержатся в целом ряде эколого-фаунистических работ, среди которых здесь укажем лишь крупные монографические сводки по осам-веспидам [Blüthgen, 1961;Spradbery, 1973], а также специальные статьи [Haeseler, 1975[Haeseler, , 1978[Haeseler, , 1980[Haeseler, , 1997Kurzenko, 1980;Larionov, Senchilo, 2000;Schneider, Feitz, 2001;Larionov, Voblenko, 2002;Fateryga, 2010Fateryga, , 2011Fateryga, , 2012Ogol, Yaroshenko, 2010;Fateryga, Ivanov, 2012]. Анализируя данные работы, можно в общем виде определить основной круг кормовых растений для отдельных видов ос, а также проследить более сложные антэкологические связи, в частности набор опылительных стратегий, имеющийся у некоторых ос-веспид в отношении, например, семейства орхидных и норичниковых.…”
unclassified